Mice Lacking the Alpha9 Subunit of the Nicotinic Acetylcholine Receptor Exhibit Deficits in Frequency Difference Limens and Sound Localization - Clause, Amanda; Lauer, Amanda M.; Kandler, Karl (Frontiers in Cellular Neuroscience, 2017)
Sound processing in the cochlea is modulated by cholinergic efferent axons arising from medial olivocochlear neurons in the brainstem. These axons contact outer hair cells in the mature cochlea and inner hair cells during development and activate nicotinic acetylcholine receptors composed of α9 and α10 subunits. The α9 subunit is necessary for mediating the effects of acetylcholine on hair cells as genetic deletion of the α9 subunit results in functional cholinergic de-efferentation of the cochlea. Cholinergic modulation of spontaneous cochlear activity before hearing onset is important for the maturation of central auditory circuits. In α9KO mice, the developmental refinement of inhibitory afferents to the lateral superior olive is disturbed, resulting in decreased tonotopic organization of this sound localization nucleus. In this study, we used behavioral tests to investigate whether the circuit anomalies in α9KO mice correlate with sound localization or sound frequency processing. Using a conditioned lick suppression task to measure sound localization, we found that three out of four α9KO mice showed impaired minimum audible angles. Using a prepulse inhibition of the acoustic startle response paradigm, we found that the ability of α9KO mice to detect sound frequency changes was impaired, whereas their ability to detect sound intensity changes was not. These results demonstrate that cholinergic, nicotinic α9 subunit mediate, transmission in the developing cochlear plays an important role in the maturation of hearing.